Hydrology affects shorebirds, waterfowl, and other waterbirds at Bear River Bay, a Globally Important Bird Area. Issue 4 (8th November 2021) - Tavernia, Brian G.; Meehan, Tim; Neill, John; Luft, John
Abstract: The value of saline lakes and associated wetlands as habitats in the xeric Great Basin is dependent on having water of sufficient quantity and quality to support wetland‐dependent birds. To inform conservation and management of these habitats, models are needed to link birds and hydrological changes due to climate and human water use. We modeled seasonal relationships between counts for 35 migratory shorebird, waterfowl, and other waterbird species or taxonomic groups and hydrological metrics at Bear River Bay, a globally Important Bird Area at Utah's Great Salt Lake. We found that increased fall surface flows to the bay increased counts of 13 species, including American Avocets ( Recurvirostra americana ), American White Pelicans ( Pelecanus erythrorhynchos ), American Wigeons ( Mareca americana ), Northern Pintail ( Anas acuta ), Redheads ( Aythya americana ), and Ruddy Ducks ( Oxyura jamaicensis ). Increased spring surface flows increased counts of Forster's Terns ( Sterna forsteri ) and the sandpiper group, whereas intermediate spring flows produced peak counts for American White Pelicans. Thus, conservation or management actions that increase seasonal flows to Bear River Bay are expected to increase bay use by diverse members of the avian community. Counts for 11 species or taxonomic groups responded positively or negatively to the seasonal elevation of Great Salt Lake, and these responses are hypothesized to reflect the relative availability of habitats within the bay versus the lake as a whole. Our models provide tools that allow managers to understand how hydrological changes associated with climate change and human water use will affect birds in Bear River Bay. Addressing lake‐wide and regional population implications of changing hydrological conditions at Bear River Bay, Great Salt Lake, and other locations across the Great Basin will require a regionally coordinated assessment of hydrology, habitat, and bird movements in response to changing habitat conditions. RESUMEN: La hidrología afecta aves playeras, anátidas y otras aves acuáticas en Bear River Bay, una Área de Importancia Global para las Aves El valor como hábitat de los lagos salinos y humedales asociados en el Great Basin xérico depende de tener suficiente calidad y cantidad de agua para dar soporte a las aves dependientes de humedales. Para informar la conservación y el manejo de estos hábitats, se necesitan modelos que vinculen a las aves con los cambios hidrológicos relacionados al clima y el uso humano del agua. Modelamos la relación estacional entre los conteos de 35 aves playeras, anátidas y otras especies acuáticas migratorias o grupos taxonómicos, y métricas hidrológicas en Bear River Bay, un Área de Importancia para las Aves en el Great Salt Lake de Utah. En otoño, encontramos que el incremento de flujos de superficie a la bahía aumentó los conteos de 13 especies, incluyendo a Recurvirostra americana, Pelecanus erythrorhynchos, Mareca americana, Anas acuta, Aythya americana y Oxyura jamaicensis . En primavera, el incremento de los fujos de superficie aumentó los conteos de Sterna forsteri y varios playeros, mientras que los flujos intermedios produjeron conteos pico de Pelecanus erythrorhynchos . Por ello, se espera que las acciones de conservación o manejo que incrementen los flujos estacionales a Bear River Bay a su vez aumente el uso de la bahía por diversos miembros de la comunidad de aves. Los conteos de 11 especies o grupos taxonómicos respondieron positiva o negativamente a la elevación estacional del Great Salt Lake y tenemos la hipótesis de que estas respuestas reflejan la disponibilidad relativa de hábitats al interior de la bahía versus la del lago completo. Nuestros modelos proveen herramientas que permiten a los gestores entender cómo los cambios hidrológicos asociados con el cambio climático y el uso humano del agua afectarán a las aves en Bear River Bay. Entender las implicaciones del cambio de condiciones hidrológicas en todo el lago y en poblaciones regionales de Bear River Bay, Great Salt Lake, así como en otras localidades a lo ancho del Great Basin, requerirá de una caracterización regionalmente coordinada de la hidrología, hábitat y movimientos de las aves en respuesta a las cambiantes condiciones de sus hábitats.